2017
DOI: 10.1088/2051-672x/aa7931
|View full text |Cite
|
Sign up to set email alerts
|

Fractographic correlations with mechanical properties in ferritic martensitic steels

Abstract: The ultimate continuum of a material is nothing but the process called fracture. Fracture surface retains the imprint of the entire deformation history undergone in a material. Hence, it is possible to derive the approximate deformation and fracture properties of a material from a systematic fracture feature analysis. There has been large volume of literature available in the open domain correlating different mechanical and fracture responses of reduced activation ferritic martensitic grade steels under variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 206 publications
0
3
0
Order By: Relevance
“…This kind of layer with continuous shear marks (also termed as transfer layer) is typically observed in the higher FC range. 44,53,54 Further, the rolling marks found to be intact on the surface can be seen for lower FC. However, there are no such marks for higher FC, which indicates a higher wrap angle for higher FC.…”
Section: Effect Of Friction On Joint Geometrymentioning
confidence: 82%
“…This kind of layer with continuous shear marks (also termed as transfer layer) is typically observed in the higher FC range. 44,53,54 Further, the rolling marks found to be intact on the surface can be seen for lower FC. However, there are no such marks for higher FC, which indicates a higher wrap angle for higher FC.…”
Section: Effect Of Friction On Joint Geometrymentioning
confidence: 82%
“…Elongated dimples are related to the direction of the applied stress. Cavitation during creep is the cause of the extensive dispersion of fine dimples and indicates the level of intergranular fracture [ 57 ]. Very fine dimples are related to the presence of reinforcements in the matrix.…”
Section: Resultsmentioning
confidence: 99%
“…Then, Goods and Brown reviewed the theories of void nucleation [6], including the void nucleation mechanisms derived from plastic deformation at grain boundaries, inclusions, and second-phase particles. Das and Chakravartty [7] have provided a comprehensive literature review of the different void nucleating sites for various alloys, indicating that micro voids intermittently form from a variety of elastic discontinuities such as inclusions, second phases, grain boundaries, etc. In an early review by Curran et al [8], experimentally observed nucleation sites of voids were listed along with their associated nucleation mechanisms and loading parameters.…”
Section: Introductionmentioning
confidence: 99%